Dynamics of Intraseasonal Sea Level Variations Observed at Gan Island and Sibolga - Iskhaq Iskandar (Jurnal Matematika & Sains, 2009)
Dynamics of intraseasonal sea level variability in the central and eastern equatorial Indian Ocean is examined using 66 months (1 January 1993 to 30 June 1998) of the observed sea level at Gan Island (0°41S, 73°E) and Sibolga (1°45N, 98°46E). The analysis shows that the intraseasonal signals of 20-100-day at those two tidal stations are coherent and exhibit eastward energy propagation. These intraseasonal variations are associated with the propagation of equatorial Kelvin waves generated by the zonal winds along the equator. The lag-correlation analysis reveals that their phase speed is closed to the theoretical phase speed of the first and second baroclinic modes of the Kelvin waves.